A la búsqueda del concepto de diplomacia bizantina - Bádenas de la Peña, Pedro (Byzantion Nea Hellás, 2015)
In popular sense the word "Byzantine" is synonimous with deviousness anddipomatic intrigue, but the Byzantine diplomacy was in fact very complex and pragmatic. The aim of this paper is to contribute precisely to the research of Byzantine diplomacy, a field still lacking a comprehensive and systematic investigation. We intend here to survey the notion of Byzantine diplomacy taking into account the geopolitical context of the empire. From the specific particularities in the time and the space we try to explain the overall pattern of the foreign policy in Byzantium; we introduce distinctions into ’foreign affairs’ and ’diplomacy’ and we examine the changing diplomatic practices, always subordinate to a defensive.